Influences of Zn Concentration on Dielectric Properties of ZnxNi1-xFe2O4 Magnetic Nanoparticles - Suharyadi, Edi; Rahayu, Dwi Indah; Armitasari, Linda; Abraha, Kamsul (UI Scholars Hub, 2018)
Dielectric properties of ZnxNi1-xFe2O4magnetic nanoparticles (MNPs) with various Zn concentration (x = 0.2-0.8) havebeen investigated over a wide frequency range 5–120 kHz. Zn-Ni ferriteMNPs have spinel cubic structure. Thecrystallite size of the sample for x = 0.2 was about 21.5 nm and then decreases by increasing Zn concentration. For sample with x = 0.4 at frequency 20 kHz, the real dielectric constant (ε') was 35.9, imaginary dielectric constant (ε